2017
DOI: 10.1017/s0007114516001239
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness and shapes of subcortical brain structures in children

Abstract: A few studies have recently reported that higher cardiorespiratory fitness is associated with higher volumes of subcortical brain structures in children. It is, however, unknown how different fitness measures relate to shapes of subcortical brain nuclei. We aimed to examine the association of the main health-related physical fitness components with shapes of subcortical brain structures in a sample of forty-four Spanish children aged 9·7 (sd 0·2) years from the NUtraceuticals for a HEALthier life project. Card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 53 publications
(92 reference statements)
6
31
0
3
Order By: Relevance
“…There has been speculation that coordination exercise might influence the brain structure differently than aerobic exercise (Voelcker‐Rehage & Niemann, ). Yet, our null result is consistent with the results of a previous experimental study focused on the shape of subcortical brain structures in children (Ortega et al, ) and in obesity (Esteban‐Cornejo et al, ). Notably, we should interpret these null results with caution because the sample size in the present study is relatively small.…”
Section: Discussionsupporting
confidence: 93%
“…There has been speculation that coordination exercise might influence the brain structure differently than aerobic exercise (Voelcker‐Rehage & Niemann, ). Yet, our null result is consistent with the results of a previous experimental study focused on the shape of subcortical brain structures in children (Ortega et al, ) and in obesity (Esteban‐Cornejo et al, ). Notably, we should interpret these null results with caution because the sample size in the present study is relatively small.…”
Section: Discussionsupporting
confidence: 93%
“…The association between watching TV and gray matter volume was independent of cardiorespiratory fitness, whereas for playing video games one of the three brain regions was no longer significantly associated (i.e., the right inferior temporal gyrus), and for total sedentary time both regions (i.e., the cerebellum crus I and crus II) were not significantly associated after additional adjustment for cardiorespiratory fitness. This may be related to previous studies showing that cardiorespiratory fitness is positively associated with the structure of the preadolescent human brain [24][25][26]42]. For example, in a previous study with the present sample we found that higher cardiorespiratory fitness was related to greater gray matter volume in the frontal regions (i.e., the premotor cortex and the medial primary motor cortex), the subcortical nuclei (i.e., the hippocampus and the caudate), the temporal regions (i.e., the inferior temporal gyrus and the parahippocampal gyrus) and the calcarine cortex [26].…”
Section: Discussionsupporting
confidence: 74%
“…Chaddock et al found that children with higher cardiorespiratory fitness had greater volume of the hippocampus and the dorsal striatum of the basal ganglia (i.e., the caudate, the putamen and the globus pallidus) than less fit children [24,25]. Ortega et al found that children with higher cardiorespiratory fitness had enlarged regions in the amygdala, the hippocampus, the bilateral putamen and the pallidum [42]. Therefore, cardiorespiratory fitness may play a role in the associations between sedentary behaviors and gray matter volume in children.…”
Section: Discussionmentioning
confidence: 99%
“…Herting et al studied male adolescents (15-18 years old) and found that the level of aerobic fitness correlated with left hippocampus volume [14] and with right rostral middle frontal cortical volume [15]. In children, aerobic fitness has been demonstrated to associate with several subcortical regions, such as the hippocampus and basal ganglia [16][17][18][19][20]. In addition, exploratory analysis by Chaddock-Heyman et al [21] proposes that more highly fit children may have decreased cortical thickness in superior frontal cortex, superior temporal areas, and lateral occipital cortex.…”
Section: Accepted Manuscript 1 Introductionmentioning
confidence: 99%